Donation motivations: testing theories of access and ideology - Barber, Michael (2016)
Understanding why donors give money to legislative candidates is vital for assessing how money influences politics. In this paper, I test theories of why political action committees (PACs) and individuals, the two largest sources of campaign money, contribute to legislative candidates. Using a variety of data at the state and federal level, I show dramatic differences between individual and PAC contribution patterns. An original survey of donors in the 2012 election cycle shows that individuals consistently rank ideological concerns as highly important when deciding where to give. Finally, using two different within-legislator designs, I show a causal relationship between incumbency, ideology, and contributions. These results provide the most direct and comprehensive test of contributor motivations to date.
Keywords: Elections